Monitoring interfacial electric fields at a hematite electrode during water oxidation. Issue 12 (3rd March 2023) - Saeed, Khezar H.; Garcia Osorio, Dora-Alicia; Li, Chao; Banerji, Liam; Gardner, Adrian M.; Cowan, Alexander J.
Abstract : Electric field induced second harmonic generation spectroscopy is used to monitor the potential drop across the space-charge and Helmholtz layers in a hematite electrode during water oxidation. Abstract : To understand the mechanisms of water oxidation on materials such as hematite it is important that accurate measurements and models of the interfacial fields at the semiconductor liquid junction are developed. Here we demonstrate how electric field induced second harmonic generation (EFISHG) spectroscopy can be used to monitor the electric field across the space-charge and Helmholtz layers in a hematite electrode during water oxidation. We are able to identify the occurrence of Fermi level pinning at specific applied potentials which lead to a change in the Helmholtz potential. Through combined electrochemical and optical measurements we correlate these to the presence of surface trap states and the accumulation of holes (h + ) during electrocatalysis. Despite the change in Helmholtz potential as h + accumulate we find that a population model can be used to fit the electrocatalytic water oxidation kinetics with a transition between a first and third order regime with respect to hole concentration. Within these two regimes there are no changes in the rate constants for water oxidation, indicating that the rate determining step under these conditions does not involve electron/ion transfer, in-line with it being O–O bond formation.